Out of my mind - Draper, Sharon M. (Sharon Mills) (Atheneum Books for Young Readers, 2012)
Considered by many to have intellectual disabilities, a brilliant, impatient fifth-grader with cerebral palsy discovers a technological device that will allow her to speak for the first time.